Glioma cancer stem cells modulating the local tumor immune environment - Khan, Imran; Mahfooz, Sadaf; Karacam, Busra; Elbasan, Elif Burce; Akdur, Kerime; Karimi, Hasiba; Sakarcan, Ayten; Hatiboglu, Mustafa Aziz (Frontiers in Molecular Neuroscience, 2022)
Glioma stem cells (GSCs) drive the resistance mechanism in glioma tumors and mediate the suppression of innate and adaptive immune responses. Here we investigate the expression of mesenchymal-epithelial transition factor (c-Met) and Fas receptor in GSCs and their role in potentiating the tumor-mediated immune suppression through modulation of tumor infiltrating lymphocyte (TIL) population. Tumor tissues were collected from 4 patients who underwent surgery for glioblastoma. GSCs were cultured as neurospheres and evaluated for the co-expression of CD133, c-Met and FasL through flow cytometry. TILs were isolated and evaluated for the lymphocyte subset frequencies including CD3 +, CD4 +, CD8 +, regulatory T cells (FOXP3 + CD25) and microglia (CD11b + CD45) using flow cytometry. Our findings revealed that a significant population of GSCs in all four samples expressed c-Met (89–99%) and FasL (73–97%). A significantly low microglia population was found in local immune cells ranging from 3 to 5%. We did not find a statistically significant correlation between expressions of c-Met + GSC and FasL + GSC with local and systemic immune cells. This may be regarded to the small sample size. The percent c-Met + and FasL + GSC population appeared to be related to percent cytotoxic T cells, regulatory T cells and microglia populations in glioblastoma patients. Further investigation is warranted in a larger sample size.